Nigeria’s Electricity Power Sector Reform: An Appraisal of Unresolved Issues. - Idowu, Samuel S.; Ibietan, Jide; Olukotun, Ayo (International Journal of Energy Economics and Policy, 2019)
Nigeria electricity sector reform was perceived as essential due to its undesirable state, consequently, it was embraced by the populace with a high expectation that it would mark the end of epileptic electricity supply. However, the low level of generating capacity and sanctity of the privatization process alongside the poor quality of DISCOs post-privatisation power supply make one worrisome about the efficacy of the reform. This article, therefore, evaluate germane issues hampering the delivery of positive deliverable especially, that of stable power supply and smooth operation of the sector. The study explores secondary data sources and system theory as the underpinning framework. It found out that capital investment, technical losses, national grid system, enabling environment, high debt profile and politicization of the power sector, amongst others, are challenges besetting the actualization of the reform objectives. Hence, to overcome these problems, the work recommends a holistic liberalization of the sector, proactive regulatory agency, metering of customers and sound economic management to reduce the poverty levels of citizens amongst others. Keywords: Electricity, Nigeria, Reform. JEL Classifications: H DOI: https://doi.org/10.32479/ijeep.8232